Deposit Mobilization, Fund Utilization and Operating Performance: The Case of the Tabung Haji Malaysia - W Mahmood, W. M.; Misban, L.E (Universiti Sains Islam Malaysia, 2024)
This study examines and evaluates deposits mobilization, fund utilization and operating performance of Tabung Haji Malaysia. The deposits mobilization measures the sources of saving scheme offered while the fund utilization measures the use of mobilize fund of Tabung Haji. The study also investigates the operating performance of Tabung haji measured by Return on Asset (ROA), Return on Equity (ROE), Current Asset (CR) and Current Assets Ratio (CAR). The study finds that Tabung Haji has absorbed most of the deposits available to profitability investment and financing strategy between 1990 through 2000. However, after 2000, the institution has not fully utilizing the available fund With regards to its operating performance, we observe that the Tabung Haji as an institution which provides services such as pilgrimage, finance and investment to its depositor is operationally and financially sound, and credible.